1996
DOI: 10.1002/j.1552-4604.1996.tb04193.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food on the Relative Bioavailability of Oral Ganciclovir

Abstract: The steady-state pharmacokinetics of oral ganciclovir in the fasting versus fed state were studied in 20 patients infected with human immunodeficiency virus and with a seropositive test result for cytomegalovirus in a two-way crossover study. Patients received oral ganciclovir at a dose of 1000 mg every 8 hours for 8 days. On days 4 and 8, subjects were randomly assigned to receive the morning dose either after an overnight fast or after a standardized 602-calorie, high-fat (46.5%) breakfast. Serial blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…In regard to food effects, gancyclovir is known to exhibit a small (20% increase) but significant food effect at 1000 mg,101 but in a separate study, showed a larger, more significant doubling of AUC with food at 2000 mg 102. At conventional doses acyclovir (3 × 200 mg dosed 4 h apart) shows equivalent AUCs fasted and fed,98 although a high fat meal has been shown to slightly reduce (by about 18%) the extent of oral absorption of a 400 mg dose compared to a low fat meal 103.…”
Section: Results‐selected Example Drugsmentioning
confidence: 99%
“…In regard to food effects, gancyclovir is known to exhibit a small (20% increase) but significant food effect at 1000 mg,101 but in a separate study, showed a larger, more significant doubling of AUC with food at 2000 mg 102. At conventional doses acyclovir (3 × 200 mg dosed 4 h apart) shows equivalent AUCs fasted and fed,98 although a high fat meal has been shown to slightly reduce (by about 18%) the extent of oral absorption of a 400 mg dose compared to a low fat meal 103.…”
Section: Results‐selected Example Drugsmentioning
confidence: 99%
“…Oral absorption of ganciclovir is delayed, with a time to peak concentration T max ranging between 2 and 14 h, depending on the type of transplanted organ and the conditions under which the medication is administered [13][14][15][16] . Absorption of ganciclovir is also erratic and incomplete, with a mean bioavailability of 4.5 % ( ± 1 %) under fasting conditions [17] .…”
Section: Absorption and Distributionmentioning
confidence: 99%
“…Absorption of ganciclovir is also erratic and incomplete, with a mean bioavailability of 4.5 % ( ± 1 %) under fasting conditions [17] . The rate and extent of ganciclovir absorption is greatly affected by food, particularly meals high in fat [15] . An open-label, randomized, crossover study was conducted in patients who were seropositive for both human immunodeficiency virus (HIV) and CMV.…”
Section: Absorption and Distributionmentioning
confidence: 99%
“…Assim, é de fundamental importância conhecer as substâncias ativas cuja velocidade de absorção e/ou quantidade são alteradas, bem como aquelas que não são afetadas pela presença de nutrientes (Toothaker & Welling, 1980). Estudos aprofundados com humanos sobre estes mecanismos têm sido realizados, com a finalidade de demonstrar mais precisamente os efeitos dos nutrientes sobre a biodisponibilidade dos fármacos (Radulovic et al, 1995;Lavelle et al, 1996). Analgésicos e antiinflamatórios, por exemplo, são com freqüência administrados com alimentos.…”
Section: N T R O D U ç ã O I N T R O D U ç ã O I N T R O D U ç ã O unclassified